2021
DOI: 10.1155/2021/9928282
|View full text |Cite
|
Sign up to set email alerts
|

Based on Network Pharmacology and Molecular Docking to Explore the Underlying Mechanism of Huangqi Gegen Decoction for Treating Diabetic Nephropathy

Abstract: Background. Huangqi Gegen decoction (HGD), a Chinese herb formula, has been widely used to treat diabetic nephropathy in China, while the pharmacological mechanisms are still unclear. Therefore, the present study aims to explore the underlying mechanism of HGD for treating diabetic nephropathy (DN). Materials and Methods. Traditional Chinese Medicine Systems Pharmacology Database (TCMSP), UniProt, and SwissTargetPrediction databases were used to search the active ingredients and potential targets of HGD. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A pharmaceutical experiment also proves that metformin increases the production of VEGFA in podocytes to reduce proteinuria through hypoxia-inducible factor-2 α -VEGFA signaling pathway [ 21 ]. And a network pharmacology research shows that Huangqi Gegen decoction whose clinical efficacy has been widely confirmed [ 22 ] can bind with VEGFA to play the role of anti-inflammatory, antiapoptosis, antioxidation, and autophagy effects to improve renal function, thus delaying the development of DN [ 23 ]. All of these researches prove that VEGFA is beneficial to the establishment and maintenance of glomerular structure and function and provide a novel molecular mechanism for protecting renal function.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmaceutical experiment also proves that metformin increases the production of VEGFA in podocytes to reduce proteinuria through hypoxia-inducible factor-2 α -VEGFA signaling pathway [ 21 ]. And a network pharmacology research shows that Huangqi Gegen decoction whose clinical efficacy has been widely confirmed [ 22 ] can bind with VEGFA to play the role of anti-inflammatory, antiapoptosis, antioxidation, and autophagy effects to improve renal function, thus delaying the development of DN [ 23 ]. All of these researches prove that VEGFA is beneficial to the establishment and maintenance of glomerular structure and function and provide a novel molecular mechanism for protecting renal function.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Oral bioavailability ≥ 30% and drug-likeness ≥ 0.18 were used as the criteria to screen the active ingredients. [12] Then, the related targets of active ingredients of LGZGD were retrieved from the Traditional Chinese Medicine Systems Pharmacology Database. The Swiss Target Prediction database (www.swisstargetprediction.ch) was used to supplement the ingredients with missing targets, and obtained the targets with the top probability values.…”
Section: Methodsmentioning
confidence: 99%
“…[1,17] The corresponding drugs were then searched in the Genecards database, and protein targets were collected. [14]…”
Section: Selection Of Standard Drugs For Acne and Collection Of Relat...mentioning
confidence: 99%